Role of symbiotic microbiota dysbiosis in the progression of chronic kidney disease accompanied with vascular calcification - Sun, Mengying; Fang, Yilong; Zheng, Jianhua; Shi, Guojuan; Guo, Junli; Zhang, Xinzhou; Zhang, Rui (Frontiers in Pharmacology, 2024)
Background: Chronic kidney disease (CKD) is now globally recognized as a critical public health concern. Vascular calcification (VC) represents a significant risk factor for cardiovascular events in individuals with CKD. It is the accessible and precise diagnostic biomarkers for monitoring the progression of CKD and the concurrent VC are urgently needed.The adenine diet-induced CKD rat model was utilized to investigate chronic kidney injury, calcification in the kidney and thoracic aorta, and dysregulation of biochemical indices.Enzyme-linked immune sandwich assays were employed to analyze changes in calcificationrelated proteins. 16S rRNA sequencing was performed to delineate the microbiota characteristics in the gut and blood of CKD-afflicted rats. Additionally, transcriptome sequencing of kidney tissue was conducted to explore the relationship between CKD-associated microbiota features and alterations in kidney function.The adenine diet-induced CKD inhibited body weight gain, and led to kidney injury, and pronounced calcification in kidney and thoracic aorta. The microbiota both in the gut and blood of these affected rats exhibited significantly lower alpha diversity and distinctive beta diversity than those in their healthy counterparts. CKD resulted in dysregulation of several biochemical indices (including elevated levels of creatinine, low-density lipoprotein-cholesterol, sodium, phosphorous, total cholesterol, and urea and decreased levels of albumin, calcium, lactate dehydrogenase, and total bilirubin). Moreover, it upregulated calcification-related factors (bone sialoprotein [BSP], Klotho, fibroblast growth factor [FGF]-23, and sclerostin [SOST]) and lipopolysaccharide (LPS). Notably, the increased Acinetobacter in the blood was positively associated with calcifications in the kidney and thoracic aorta, in addition to the positive correlation with gut microbiota. The enrichment of Acinetobacter was concurrent with increases in calcification factors (BSP, FGF-23, and SOST), LPS, and phosphorous. Furthermore, transcriptome sequencing revealed that the enrichment of Acinetobacter was positively correlated with the majority of upregulated genes and negatively correlated with downregulated genes involved in the mineral absorption pathway.Our findings, for the first time, underscore that dysbiosis of symbiotic microbiota, both in the gut and blood, is involved in the progression of CKD. Particularly, the enrichment of Acinetobacter in blood emerges as a potential risk factor for CKD and its accompanying VC.